The provision of global liquidity: The global reserve system - José Antonio Ocampo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper analyses three major problems of the current international monetary system: the asymmetric-adjustment problem, dependence on the monetary policy of the main reserveissuing country, and the large demand for self-insurance by developing countries. It then proposes two reform routes: transforming it into a fully-fledged multicurrency reserve system or placing at the centre the only truly global reserve asset, the special drawing rights (SDRs). Mixing the two routes may be the only way forward. Under a mixed system, SDRs would become the source of financing for International Monetary Fund lending, but national/regional currencies would continue to be used as international means of payment and stores of value.
Keywords: F02; F33; 330; global currencies; special drawing rights; International Monetary Fund